Development of an Automation and Control System for Bovine Semen Freezing - Arango T., Jhon E.; Durán, Cristhian M.; Lizarazo, Jhon E.; Duarte, Jorge A. (TECCIENCIA, 2017)
The freezing of bovine semen (cryopreservation) consists in reducing the temperature of the sample until the point of biological stability. This freezing process is carried out by immersing the semen samples into liquid nitrogen (LN2). When a sample is submerged, it enters into a boiling regime due to the large difference in temperatures between the sample and the liquid nitrogen (LN2), causing evaporation and crystallization. Freezing curves for biological samples of bovine semen are rarely found in scientific literature; however, there are several rhythms of freezing that have been manually carried out and have achieved acceptable results. The main objective of this study is to design and implement an automated control system of freezing bovine semen that can follow or simulate the ideal freezing curves for optimal freezing after stabilization